A Design of Multichannel Data Transmission Through Power Line Communication - Kavitha, A; Prabhu, V; Ruban Thomas, D; Banupriya, D; Dharanya, S; Roobini, M (International Journal of Engineering and Technology, 2018)
Smart Metering in the power grid is the present popular technology in and around the world.  Future Generation is requiring new method for data transfer. This paper introduces a novel method called Power Line Communication (PLC) transceivers. PLC has many number of smart grid applications. This work proposes  mainly about the transmission of data’s through Power Line.   This work includes both electrical and electronic concept. Here, transmission process takes place through electrical line by using electronic equipment. This paperaddresses the important role of  transferring data’s from one place to other. In this concept, dc loads are controlled by giving commands through power line. This work does not require additional medium for transmitting data’s. This paper reduces the human efforts and systematic transmission takes place.  In this work, data transmission through power line communication takes place by passing constant 5v. Hence fluctuations are avoided in PLC transceivers, this protects the electronic device and dc load from damage.  Here the dc loads are operated by giving ON and OFF commands.  These commands can be coded in binary form or it can also be variables.  Voltage sensors are used for sensing the current at the receiver (dc loads).  The current which is sensed by the sensors are stored by using batteries. These currents can be retrieved for future use. This paperprovides advancement in data transmission process for future generation.